Contemporary Issues in Women's Health. Issue 1 (1st March 2020) - Geary, Michael; Chibwesha, Carla; Stringer, Elizabeth
Abstract : Should we give prophylactic antibiotics routinely after operative vaginal delivery? Delivering better maternity care experiences across public health systems in low‐ and middle‐income countries PROLONG Study shows no benefit from 17‐hydroxyprogesterone in preventing recurrent spontaneous preterm birth.